Pendidikan Agama Kristen Dalam Keluarga: Pengembangan Nilai Mealtable Sharing Terhadap Keharmonisan Hubungan Kasih Antara Orang Tua dan Anak Di Jemaat Gmim Bukit Sion Mapanget - Farly Rolando Roringpandey; Netanel Kaunang; Semuel Selanno (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2022)
The purpose of this study is to describe and analyze the development of the values ​​contained in Mealtable Sharing related to the value of harmony in the family, the process of developing the value of mealtable sharing in the GMIM Bukit Sion Mapanget Congregation in relation to the harmonious relationship of love between parents and children, Inhibiting factors in the process of developing the Value of Mealtable Sharing on the Harmony of Love Relationships between Parents and Children in the GMIM Bukit Sion Mapanget Congregation, and the efforts made by parents and Church leaders in overcoming the inhibiting factors related to the development of the Value of Mealtable Sharing on Harmony The Relationship of Love between Parents and Children in the GMIM Bukit Zion Mapanget Congregation. This research method is a descriptive qualitative research conducted at the GMIM Bukit Sion Mapanget Congregation. Data were collected through observation, interviews and documentation studies. From the results of the analysis and interpretation of the data obtained that: (1). Eating together and talking together "mealtable sharing" is often done by families in which there is an atmosphere to give love to each other, is a place for teaching and educating children, can strengthen harmonious relations between parents and children and can improve children's development. The values ​​found when sitting down to eat together include togetherness, respect, harmony, gratitude for the blessings that God has given so as to create a harmonious loving relationship between parents and children. (2). The inhibiting factors are the lack of parental time due to busy work and the distance that separates them, the child's lack of trust in parents, and the presence of technological developments that limit the interaction between parents and children. (3). There is also the role of parents by providing time from a lot of busy work, creating a comfortable atmosphere and teaching about wisdom in using cellphones. (4). There is also the role of Church leaders through preaching and pastoral services to be able to direct the understanding of parents to be examples and role models, take advantage of technological sophistication, introspect themselves, and rebuild trust with children. From the results of data exposure, findings, and discussion, it is necessary for parents and families to understand the importance of sitting down to eat and talk together at the dining table so that they can strengthen the harmonious loving relationship between parents and children.